1977
DOI: 10.1029/jb082i023p03369
|View full text |Cite
|
Sign up to set email alerts
|

Postseismic crustal uplift near Anchorage, Alaska

Abstract: Results of four leveling surveys carried out by the National Geodetic Survey between Anchorage and Whittier, Alaska, combined with an analysis of sea level measurements at Anchorage, indicate as much as 0.55 m of land uplift in the decade following the 1964 Prince William Sound earthquake. The pattern of uplift is parabolic in shape, convex upward, and reaches a maximum approximately halfway between Anchorage and Whittier, or about 300 km northwest of the Aleutian trench axis. The data suggest that the positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 29 publications
6
76
0
2
Order By: Relevance
“…2.1.7, right panel). Evidence for this feature was noted as early as Brown et al (1977), but a definitive explanation has not been proposed. As Larsen et al (2003) noted, it is possible to explain this feature in terms of propagating slip pulses on the megathrust, although any such model would be very poorly constrained.…”
Section: Decadal Scale Vertical Velocity Fieldmentioning
confidence: 99%
See 3 more Smart Citations
“…2.1.7, right panel). Evidence for this feature was noted as early as Brown et al (1977), but a definitive explanation has not been proposed. As Larsen et al (2003) noted, it is possible to explain this feature in terms of propagating slip pulses on the megathrust, although any such model would be very poorly constrained.…”
Section: Decadal Scale Vertical Velocity Fieldmentioning
confidence: 99%
“…Observations post 1964 indicate ~0.3 m land uplift by 1975 (Brown et al, 1977) and 0.7 m by 1995-2000 (Freymueller et al, 2008) …”
Section: Portage Garagementioning
confidence: 99%
See 2 more Smart Citations
“…For the 1964 Alaskan earthquake, Brown et al ( 1977) found postseismic relaxation effects with a time scale on the order of 5 years. As shown in Figure 3.2, a large fraction of the vertical displacements occurred in the first year after the earthquake; it is not clear from the data how much of this early displacement is related to aftershocks, or whether there might be crustal relaxation processes on a time scale shorter than 5 years.…”
Section: Stations Should Be Established With a Spacing Of 50 Km Alongmentioning
confidence: 99%